Temporal lobe "plus" epilepsy associated with oligodendroglial hyperplasia (MOGHE). (8th July 2019) - Garganis, Kyriakos; Kokkinos, Vasileios; Zountsas, Basilios; Dinopoulos, Argirios; Coras, Roland; Blümcke, Ingmar
Abstract : Background: Mild malformation of cortical dysplasia (mMCD) with oligodendroglial hyperplasia (MOGHE) is an epilepsy‐related pathologic entity highlighted in post‐surgical specimens of frontal lobe epilepsy (FLE) patients. Aims of the Study: We present two temporal lobe epilepsy (TLE) cases with MOGHE and discuss clinical, neurophysiological, and neuroimaging features that may be indicative of surgical outcome. Methods: We identified two cases with MOGHE out of 30 temporal lobe epilepsy (TLE) surgical patient cohort, whose pathological distribution spared the hippocampal structures. Results: The TLE cases shared common features with the FLE series in terms of patient profiles, MRI findings and post‐surgical outcome. TLE plus seizure semiology combined with extratemporal scalp electroencephalographic (EEG) and electrocorticographic (ECoG) epileptiform elements at a distance from the imaging lesion were suggestive of an underlying multifocal pathology. Conclusions: MOGHE pathology has to be considered in the decision‐making process for TLE epilepsy surgery when this constellation of features is met.